Interactive optomechanical coupling with nonlinear polaritonic systems - Bobrovska, N. (2017)
We study a system of interacting matter quasiparticles strongly coupled to photons inside an optomechanical cavity. The resulting normal modes of the system are represented by hybrid polaritonic quasiparticles, which acquire effective nonlinearity. Its strength is influenced by the presence of a mechanical mode and depends on the resonance frequency of the cavity. This leads to an interactive type of optomechanical coupling, which is distinct from previously studied dispersive and dissipative couplings in optomechanical systems. The emergent interactive coupling is shown to generate effective optical nonlinearity terms of high order, which are quartic in the polariton number. We consider particular systems of exciton polaritons and dipolaritons, and show that the induced effective optical nonlinearity due to interactive coupling can exceed in magnitude the strength of Kerr nonlinear terms, such as those arising from polariton-polariton interactions. As applications, we show that the higher-order terms give rise to localized bright flattop solitons, which may form spontaneously in polariton condensates.